Sliding mode approach to congestion control in connection-oriented communication networks - Bartoszewicz, Andrzej; Żuk, Justyna (Wydawnictwo Politechniki Łódzkiej, 2009)
In this paper, a novel sliding mode flow controller design for the connection-oriented communication networks is proposed. The networks are modeled as discrete time systems with the available bandwidth acting as disturbance. The proposed controller is designed in such a way that the closed-loop system stability and fast, finite time error convergence are ensured. In order to avoid the problem of excessive control signal magnitude, a sliding mode controller with saturation is proposed. When this controller is applied no bottleneck link buffer overflow and full utilization of its available bandwidth are guaranteed. Furthermore, transmission rates generated by the controller are always upper bounded and nonnegative.